IMPLEMENTASI PROGRAM PENGELOLAAN SAMPAH OLEH BANK SAMPAH MITRA HARIWANG DESA PASIRLAWANG KECAMATAN PURWADADI KABUPATEN CIAMIS - Tania Ayu Wandani; Endah Vestikowati; Neti Sunarti (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
The purpose of this study was to determine the implementation of waste management programs by Mitra Hariwang Waste Bank, Pasirlawang Village, Purwadadi District, Ciamis Regency. This research uses qualitative methods with a descriptive approach. The triangulation technique of collection is done through observation, in-depth interviews, and documentation. The number of informants as many as 5 (five) people is determined through a purposive sampling process. Data processing techniques are carried out with stages of data reduction, data presentation and drawing conclusions. The results of the study stated that the existence of Ciamis Regency Regional Regulation Number 2 of 2018 concerning Waste Management is the seriousness and success of local governments in managing waste up to the local village level with waste management by waste banks. However, the reality on the ground shows that the implementation of the program has not been widely socialized to the community, lack of support for physical waste facilities, low ability of waste bank management staff, cross-sector coordination has not been carried out properly. So it requires well-organized coaching and commitment through institutionalized communication.